Implikasi Pendidikan Agama Islam Berbasis Teknologi Informasi dan Komunikasi (Studi Kasus pada Siswa SMK Al-Huda): Implications of Islamic Religious Education Based on Information and Communication Technology (Case Study on Al-Huda Vocational School Students) - Riyan Hidayatulloh; Yuliyanti Yuliyanti (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
The digital era of Society 5.0 demands the transformation of Islamic Religious Education (PAI) learning from conventional memorization to the creation of contextual digital da'wah content, but limited literature reveals the dynamics of creativity of urban Islamic Vocational School students. This study aims to describe the implementation of ICT-based Islamic Religious Education (PAI) learning and analyze its implications for the creativity of Al-Huda Kebon Jeruk Vocational School students through concrete manifestations of Blender 3D prayer videos, the "Islamic Social Media Ethics" application, and the Spotify Digital Dakwah Club tauhid podcast. This study uses a descriptive qualitative approach of participatory observation triangulation (12 blended learning sessions), in-depth interviews of Islamic Religious Education teachers, students, and managers, and analysis of offline Google Slides+USB hybrid lesson plan documentation using the Miles-Huberman model with the validity of source-technique triangulation. The results of the study show that Islamic Religious Education and Information and Communication Technology at Al-Huda Vocational School generate student creativity through hybrid project-based learning transformation (Zoom-Kahoot 60%, Powtoon project 40%), which produces authentic interdisciplinary Islamic Religious Education-TKR-TKJ da'wah content, overcoming infrastructure limitations via group hotspots and USB modules, even though students' digital literacy challenges vary, solved through gradual Canv—blender scaffolding. The study resulted in a Digital Vocational Islamic Religious Education Creativity Model and a Hybrid RPP Blueprint replicated in 247 Islamic Vocational Schools in DKI; transforming teachers from narrators to creativity facilitators; preparing competitive graduate LinkedIn portfolios of professional da'wah content; becoming a benchmark for national digital Islamic vocational education.